Uma analise da linguagem utilizada em livros didaticos de matematica do Ensino Médio - Jurama Maia (2016)
At work as a mathematics teacher in public schools observe that students have difficulties in understanding written texts, it occurs mainly in the use of textbooks where they do not dominate there this language. This work aims to identify and analyze some elements of the language used in the teaching of mathematics book. For this, to adopt the kind of linguistic analysis, we investigated a textbook high school math, more specifically the content of functions. The choice of textbook researched used as a reference guide PNLD / 2015 (National Textbook Program) and FNDE distribution ratio. It was taken as a theoretical social semiotics, in particular the work of Candia Morgan. The linguistic elements established by Morgan are: Use of Pronouns; Impersonal Function; Function Impositive and Vocabulary Specialized Mathematics (use of symbols, representational object; nominalization and forms ofschool mathematical language). This research is qualitative and analyze the statements of the book of activities to this end, the feature in three different contexts using Skovsmose, pure mathematics, semi-reality and reality. Regarding the results it can be inferred that the language presented in the statements analyzed, it uses many elements that can alienate the reader, treating it passive and authoritarian manner,using a specialized vocabulary, with symbols and nominalizations, which will not close this text reader. The product of this research is aimed at developing a didactic and formative text for math teachers, to help understand and facilitate the use of textbooks by students.